Terapi Bekam Basah Dalam Menurunkan Nyeri Leher Dan Bahu Pada Pekerja Kantor - Devi Mediarti; Lukman Lukman (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2021)
Wet cupping is a traditional complementary method recommended to reduce the symptoms of many diseases and is used in pain treatment The purpose of the study: knowing the effects of wet cupping therapy on the neck and upper shoulder pain PeneliHiin Method: 61 qualified office worker participants with nonspecific neck and upper shoulder pain complaints for 3 years Last month. The Numerical Rating Scale (NRS) is used to assess pain scores. Pain scores were measured before and after wet cupping therapy. Hasll research: The average score of pain letter in the case group of 7.02 (SD 1/4 1fi) and 3JO (SD 1/4 22) after cupping therapy. Decrease in pain before and after scores is statistically significant (p < 0.05). Discussion: It can be stated that wet cupping therapy has a potential therapeutic effect on non-specific neck and upper shoulder pain. Experimental research with respondents who have full-scale controlled pain complaints needs to be done to prove the effectiveness of this intervention.